Identification of the novel HLA‐B*27:147 allele by polymerase chain reaction sequence‐based typing. (20th April 2017) - He, J.; Zhang, W.; Han, Z.‐D.; Wang, W.; Zhu, F.‐M.
Abstract : HLA‐B*27:147 differs from HLA‐B*27:04:01 by a single nucleotide substitution at position 523 C>G.